2014
DOI: 10.1186/1476-511x-13-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment and control of dyslipidemia among adults in Northwestern China: the cardiovascular risk survey

Abstract: AimThe aim of this study was to estimate the prevalence, awareness, treatment, and control of dyslipidemia in Xinjiang, China.MethodStratified sampling method was used to select a representative sample of the general population including Chinese Han, Uygur, and Kazak in this geographic area. Seven cities were chosen. Based on the government records of registered residences, one participant was randomly selected from each household. The eligibility criterion for the study was ≥ 35 years of age.ResultsA total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 19 publications
(21 reference statements)
3
38
1
Order By: Relevance
“…The prevalence of high TC, high TG, low HDL-C, and high LDL-C was 5.11, 16.00, 19.27, and 4.76 %, respectively [15]. The prevalence of dyslipidemia among adults in northwest China was 52.72 % [16]. Similar to these results, the present study showed that the total prevalence of dyslipidemia in men was significantly higher than that in women (44.5 vs. 31.6 %), while the prevalence of high TG and low HDL-C was significantly higher than that in women.…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of high TC, high TG, low HDL-C, and high LDL-C was 5.11, 16.00, 19.27, and 4.76 %, respectively [15]. The prevalence of dyslipidemia among adults in northwest China was 52.72 % [16]. Similar to these results, the present study showed that the total prevalence of dyslipidemia in men was significantly higher than that in women (44.5 vs. 31.6 %), while the prevalence of high TG and low HDL-C was significantly higher than that in women.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, the majority of hypertensive patients (90.8%) had at least one dyslipidemia and the mixed type of dyslipidemia (greater than or equal to two lipid profile derangements) was 61.8%. Moreover, female gender was associated with raised levels of TC, LDL-c and reduced HDL-c, while hyperuricemia was associated with abnormal level of TC, TGs, HDL-c and TC/HDL-c. Studies reported that the prevalence of dyslipidemia was 52.7% and 68.7% (Luo et al, 2014;Yu et al, 2015), respectively. In addition, Framingham Heart Study indicated that more than 80% of hypertensive patients had at least one additional cardiovascular disease risk factor and mainly these risk factors were atherogenic in nature.…”
Section: Discussionmentioning
confidence: 99%
“…5 Dyslipidemia is a major risk factor for atherosclerosis, and cardiovascular disease such as coronary heart disease and stroke. [16][17][18] Increasing the awareness and knowledge of patients regarding dyslipidemia risk factors and management has a positive impact on cardiovascular disease prevention. 19 In the current study, most of the participants (77.3%) had poor knowledge regarding dyslipidemia and 47.4% had negative attitude.…”
Section: Discussion:-mentioning
confidence: 99%